DISTRIBUTION OF S-WAVE VELOCITIES AND THE POISSON COEFFICIENT IN THE LOWER CONTINENTAL CRUST - Vinnik L.P.; Mikhaylova N.G.; Boyarskiy M.E. (My University, 1988)
In this paper we discuss a continental crust section for S waves, based on data not previously used for the purpose. These are observations of waves converted from P into S waves in the lower continental crust (Ps converted waves). To interpret the resulting curve, we performed a series of numerical experiments, in which we specified a plane-stratified model of the medium in which the Thompson-Haskell method was used to synthesize theoretical seismograms. According to available data, the decrease in values of Vs at a depth of 20 km is not accompanied by a decrease in Vp. As a result, the ratio Vp/Vs at these depths is increased to at least 1.9, and the Poisson coefficient becomes greater than 0.3. Such high values of the Poisson coefficient probably result either from the predominance of hydrated basic and ultrabasic rocks at the corresponding depths or from the presence of free liquid liberated by dehydration.